Analisis dan Solusi UMKM Linedipadira D&D Boga Rasa Di Purwakarta: Pengabdian - Ikhtiar Mufti Maulana; Sulistiawati Susanto; Putri Risma Dewi; Muhammad Meki Munawar (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Community Practice and Internship Program (KPB–PKL) was conducted at UMKM Linedipadira D&D Boga Rasa, a microenterprise producing traditional nougat snacks in Plered, Purwakarta. This program focused on improving management, marketing, and financial recording systems that were still carried out in a simple manner. The main objective was to support the business owner in strengthening operational management while providing students with practical experience in applying management and accounting knowledge. The methods used included field observation, interviews, and participatory discussions to identify business conditions and existing challenges. The findings revealed several areas requiring improvement, such as digital marketing, business identity signage, and financial documentation. As follow-up actions, students assisted in creating digital marketing accounts, adding the business location on Google Maps, installing a neon box and banner, and preparing a simple bookkeeping system. The program delivered positive impacts by enhancing the professionalism of the microenterprise and strengthening students’ understanding of real business practices.